A Huge Intraabdominal Lump in a Male Patient of 32 Year with Congenital Absence of Left Testis - A Case Report - Ahmed, Nadim; Hossain, Muhammad Anowar; Hasan, Mohammad Rashedul; Islam, Mansurul; Tasnim, Afrida; Ajmir, Sah; Nahar, Nazmun (Journal of Shaheed Suhrawardy Medical College, 2019)
Undescended testis is a common risk factor for the testicular neoplasm. The risk of malignancy in an undescended testis is highest when the testis lies in the abdomen. It usually presents with a painless intraabdominal lump. Seminoma is the most common adult germ cell tumour of testis whereas Yolk sac tumour in seen in the pediatric age group. Pure yolk sac testicular tumor in an adult is extremely uncommon. Here we present a case where an adult male presented to us with a painless left sided intraabdominal lump with undescended testis on the same side was previously diagnosed as metastatic adenocarcinoma of unknown primary. In a private hospital he received three cycles of chemotherapy; but the lump did not reduce in size and he was reffered to our care for better management. The lump was excised and histopathological report revealed yolk sac tumour of left testis which is a rare presentation in adult. J Shaheed Suhrawardy Med Coll, December 2018, Vol.10(2); 115-117